Large area patterning of residue-free metal oxide nanostructures by liquid transfer imprint lithography. (21st March 2019) - Lee, Suok; Jung, Sang Hee; Jang, A-Rang; Yoon, Seong In; Shin, Hyeon Suk; Lee, Hyun Uk; Lee, JaeJong
Abstract: One-dimensional (1D) and three-dimensional (3D) residue-free metal oxide patterns are directly fabricated over large areas using liquid transfer imprint lithography (LTIL) with an ultraviolet-curable metal oxide precursor resist. A 1D line or pillar array of metal oxides nano-patterns without a residual layer is formed by LTIL and annealing processes. A 3D layer-by-layer nanomesh structure is successfully constructed by repeating the LTIL method without a complex etching process. In addition, it is possible to form a hierarchical structure in which zinc oxide nanowires are selectively grown on a desired zinc oxide (ZnO) seed pattern formed by LTIL via a hydrothermal method. Unlike the pattern fabricated by the conventional nanoimprint lithography method, in the case of the pattern formed by LTIL the residues accumulated between the patterns during the patterning procedure can be removed, and thus it is possible to easily form various types of nanostructures.